Protection of Personal Data With the Principle of Prioritizing Protecting User Privacy in an Effort to Realize Legal Goals in Indonesia - Alfred Yetno (Satya Dharma : Jurnal Ilmu Hukum, 2021)
Many Indonesian people take advantage of the development of information technology in the digital world to carry out activities and work so that not a few technologies that are currently developing to run require people's personal data so that they are vulnerable to being misused and experiencing data leaks that can harm the owner of the data. In order for this not to happen, the Government of Indonesia is obliged to protect and safeguard the personal data of the Indonesian people by protecting the privacy of the owner of the personal data from any form of misuse and leakage of personal data that can harm the Indonesian people so that the purpose of Indonesian law is to protect every Indonesian citizen's rights mandated in the 1945 Constitution can be realized and run well. In order to strengthen the current legal rules for protecting personal data and user privacy, the Indonesian government can apply the principle of prioritizing protecting personal data and user privacy which has been previously implemented by various European Union countries in the personal data protection rules known as General Data Protection. Regulation (GDPR). The application of these principles can be used in every system that exists in the digital world today that uses the public's personal data so as to avoid the possibility of misuse of personal data and leakage of personal data. and a supervisory system from the Government that becomes a single unit so that the Government of Indonesia can monitor and control the public's personal data by maintaining the security of personal data from misuse of personal data and leakage of personal data from the system and giving the community the right to monitor and control personal data related to data privacy. them so that the personal data and privacy of Indonesian users are protected and well maintained